2022
DOI: 10.3389/fmicb.2022.878856
|View full text |Cite
|
Sign up to set email alerts
|

Mating Leads to a Decline in the Diversity of Symbiotic Microbiomes and Promiscuity Increased Pathogen Abundance in a Moth

Abstract: Mating may promote microbial diversity through sexual transmission, while mating-induced immune responses may decrease it. Therefore, the study of mating-induced microbiomes changes under different mating systems is informative to unravel its biological relevance and evolutionary significance. Here, we studied the microbiomes in a community context within the abdomen of Spodoptera frugiperda females using 16S rDNA sequences by setting virgin females, and females mated once, twice, or thrice with the same or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Proteobacteria, Firmicutes and Bacteroidota are the top three dominant phyla either in male RS or female RS and gut in S. frugiperda (Fig. 4 a), which is similar to the results obtained for the female abdomen of the same species [ 45 ]. Studies in other insect species also found that Proteobacteria was the predominant phylum in gut or reproductive organs, such as in the desert locust Schistocerca gregaria [ 82 ], the citrus fruit fly Bactrocera minax [ 26 ] and the sawfly Cephalcia chuxiongica [ 83 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Proteobacteria, Firmicutes and Bacteroidota are the top three dominant phyla either in male RS or female RS and gut in S. frugiperda (Fig. 4 a), which is similar to the results obtained for the female abdomen of the same species [ 45 ]. Studies in other insect species also found that Proteobacteria was the predominant phylum in gut or reproductive organs, such as in the desert locust Schistocerca gregaria [ 82 ], the citrus fruit fly Bactrocera minax [ 26 ] and the sawfly Cephalcia chuxiongica [ 83 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our previous study in S. frugiperda using the whole abdomen of female adults provided interesting results, wherein mating caused a decline in the diversity of symbiotic microbiomes and promiscuity incurred a higher pathogen abundance [ 45 ]. In the present study, we further studied the diversity and abundance of the microbiome in the reproductive system (both male and female) and gut (female) of S. frugiperda , and mating caused changes and transmissions.…”
Section: Introductionmentioning
confidence: 99%
“…are also known to inhibit insect development, although the death rate and host immune response are different in Drosophila melanogaster infected with Providencia sneebia and P. rettgeri [ 46 ]. The abundance of beneficial microbes was higher in virgin Spodoptera frugiperda females while the abundance of pathogens, such as Morganella spp, and Serratia spp., was higher in the females mated with multiple males [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also provides critical nutrients required for normal insect physiological activity ( Nikoh et al 2011 , Salem et al 2014 ), aiding insects in the digestion of complex macromolecular substrates ( Lundgren and Lehman 2010 ). These gut microbes can also shape host movement and migration, environmental adaptability ( Tsuchida et al 2010 , Zhang et al 2021 ), insecticide resistance ( Soltani et al 2017 , Pang et al 2018 ), population genetic diversity ( Mattila et al 2012 ), mating, and reproductive behavior ( Zhang et al 2020 ).…”
mentioning
confidence: 99%
“…Moreover, the gut microbiota of S. frugiperda varies markedly when comparing different instars and adults, with certain important members of the larval microbiome being absent in adults after being lost over the course of metamorphosis and development ( Gichuhi et al 2020 , Mason et al 2020 ). The S. frugiperda gut microbiota also varies as a function of geographical distribution, mating state, and host plants ( Zhang et al 2020 , Liu et al 2021 , Chen et al 2022 , Lü et al 2022 ). In S. frugiperda subject to insecticide selection under field conditions, the composition of the gut microbiome was richer than that in resistant populations screened under laboratory conditions, with some identified microbial species being capable of metabolizing insecticides ( Gomes et al 2020 ).…”
mentioning
confidence: 99%